1927 Ark. Acts 528 - (:unkn) unknown (My University, 1927)
§ 7: Prohibited shooting fish with a gun or other instrument. Also prohibited throwing, dropping or exploding any dynamite or other explosive in the waters of the state.
Keywords: FISHING REGULATION